Improvement of teaching from improvement of assessment test: challenges - Khalid, Madihah (2010)
The impact of assessment on the teaching and learning of mathematics has been much debated and discussed. This paper will in a small part, attempt to contribute to the discussion by particularly looking at Brunei perspective. The implementation of the new education system (The National Education System for the 21st Century – SPN 21) from early 2008 has made teachers struggling with the changes to be made in the classrooms. The paper will share with participants the nature of assessment before the introduction and the desired modes of assessment proposed by both the new SPN syllabus and the primary school mathematics syllabus implemented earlier in 2006. The focus will be on the challenges faced by school teachers in implementing the desired changes especially from the point of teaching and learning. This paper will include some findings from a survey of teachers’ belief regarding assessment.